Unusual contents of a scrotal swelling. (12th May 2011) - Morris-Stiff, Gareth; Falk, Gavin A; Joyce, Daniel; Chalikonda, Sricharan
Abstract : Pseudomyxoma peritonei is an uncommon tumour, usually arising from the appendix. It occasionally presents as a hernia, particularly in men. Here, the case of a 56-year-old male with pseudomyxoma peritonei presenting as a left inguinal hernia is presented, and a brief discussion of the literature on its diagnosis and management is given. The case highlights the importance of carefully evaluating patients with ascites and abdominal wall hernias.